ANALISA KEKUATAN TARIK HASIL SPOT WELDING BAJA KARBON RENDAH - Anrinal Anrinal; Hendri Hendri (Jurnal Teknik Mesin (JTM), 2012)
The study aims to analyze the influence of time pressure on the strength of the weld connection point (spot welding) low carbon steel. The study was conducted by analyzing the tensile strength of the weld point by press time variation 20, 25, and 30 seconds on a current strength 70 Amperes. The results show that the press time will determine the outcome of a process of welding and weld strength. The longer ofpress time will result in nugget diameter (weld metal) getting bigger, and this resulted in attraction strength also increased.